Elbow fractures: current concepts. Issue 2 (March 2017) - Orvets, Nathan D.; Chamberlain, Aaron M.
Abstract : Establishing a stable and congruent joint that allows for early elbow range of motion improves outcomes in elbow fracture management. This review highlights advances in both operative and nonoperative management of common elbow fracture patterns. Advances in imaging, injury classification, surgical techniques, and implants continue to contribute to improved outcomes in elbow fracture management.